Post cholecystectomy Mirizzi syndrome: a rare complication of partial cholecystectomy as case report and review of literature - Sheth, Neil; Desai, Shivani; Yadav, Rajesh (International Surgery Journal, 2023)
Post cholecystectomy Mirizzi syndrome (PCMS) is defined as obstruction of the CHD leading to obstructive jaundice in a patient who has undergone cholecystectomy due to remnant calculus in the cystic duct or due to compression by infundibulum of gall bladder. It is a rare condition with limited cases described in literature. Herein, we describe a case of PCMS due to retained calculus in the cystic duct 12 years after cholecystectomy in a 40 year old male who presented with a 2 month history of pain fever and jaundice recurrently. Patient was diagnosed using MRCP and CT and ERCP was done but the stone could not be retrieved and patient was managed surgically and had a stable and uneventful post-operative course. As per literature reviewed there have been only 65 reported cases of PCMS and thus limited knowledge about the condition is present. Herein, we reviewed the available literature with various possible management techniques and their outcomes and also why surgical line of treatment was chosen in this case with an open approach preferred. PCMS is a rare clinical condition that requires high index of suspicion for diagnosis and can be treated with minimally invasive as well as open approach with good results and resolution of symtptoms of the patient.